Women Who Write Animals : Female Literary Representations of the More-Than-Human World - Kerslake, Lorraine; Villanueva-Romero, Diana (Nature, Culture and Literature, 2026)
Why have so many women turned to animals in their writing-and what does that reveal about our shared world? Women Who Write Animals: Female Literary Representations of the More-Than-Human World uncovers the rich, often-overlooked legacy of English-speaking female authors who, from the late 18th century to today, have written powerfully and provocatively about animals. From activists and scientists to poets and storytellers, these women reshaped how we imagine animals-and ourselves. Drawing on ecofeminism, animal studies, and posthumanist thought, the essays explore intimate bonds, political resistance, and ethical entanglements across species. With rare archival insights and through a diverse range of voices, this collection reclaims women's roles in rethinking nature, challenging readers to envision a more compassionate and interconnected planet.